Plant growth and nutrient uptake enhancement in thai dragon plant inoculated with arbuscular mycorrhizal fungi and actinomycetes - Jalaluldeen, Anfal Muayad; Agwan, Israa Muneeb; Mahmood, Abeer Ahmed; Sijam, Kamaruzaman; Al-Rejaboo, Maha Akram; Mohammed, Bilal Ahmed (Applied and Natural Science Foundation, 2026)
Soil-borne diseases pose a major threat to chili pepper production. This study investigated the synergistic effects of the arbuscular mycorrhizal fungus (AMF) Glomus mosseae and the actinomycete Streptomyces indiansis on the growth, nutrient uptake, and disease resistance of Thai Dragon pepper plants challenged with Fusarium oxysporum. A pot experiment was conducted with (8 treatments), including individual and combined inoculations. Results showed that dual inoculation significantly enhanced plant morphology and nutrient uptake (N, P, K) compared to the control. To further understand the chemical changes associated with these treatments, a GC-MS analysis was performed using a SHIMADZU QP5050A system with an injection volume of (8.000 µL).Chemical analysis revealed that plants inoculated with symbiotic mycorrhizal fungi exhibited a distinct metabolic signature. In the group not treated with symbiotic mycorrhizal fungi, difluorodimethylsilane (DFMS) was detected at a retention time of 2.425 minutes, with a similarity index of 86 and a basal peak at 81.05 m/z. In contrast, the mycorrhizal-treated group showed cyclobutane (1-methylethylenediamine) at a retention time of 2.267 minutes, with a similarity index of 73. Most notably, chloroxylenol was detected at a retention time of 29.983 minutes, with a basal peak at 121.30 m/z, a high similarity index of 81, and a total ion intensity of 550,000 counts.The combined treatment effectively reduced the severity of Fusarium wilt, likely due to the identified bioactive compounds and hydrolytic enzymes. These results demonstrate that the three-part interaction among the eight treatments supports a sustainable biological control strategy, as evidenced by significant improvements in plant biomass and the presence of prominent metabolic markers identified by GC-MS.